2005
DOI: 10.1191/0265532205lt312oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the language of young learners

Abstract: This article focuses on the plight of children as young language learners (YLLs), in the context of today’s Europe. By reference to the Council of Europe’s recommendations and its material in the form of the Common European Framework of Reference (CEFR) and the European Language Portfolio (ELP), questions are posed here as to how far the special needs of YLLs are being catered for by assessment practices in European schools. Examples are given of how the CEFR and ELP are currently used in YLL assessment, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 3 publications
0
40
0
4
Order By: Relevance
“…Hasselgreen and Moe (2006) investigated the use of conjunctions in the writing of Norwegian pupils aged 12/13 and 15/16, on levels A2 and B1, and concluded that regardless of level, the younger pupils used a distinctly narrower range of conjunctions than the older pupils. This is perhaps unsurprising, given that studies such as Nippold (2006) cited in Hasselgreen & Caudwell (2016), found that the development of conjunctions and adverbial conjuncts in English as a first language does not take off fully until adolescence. Table 2 contrasts a selection of conjunctions/adverbial conjuncts in coryl, for the different age groups.…”
Section: Interlanguage Analysismentioning
confidence: 69%
“…Hasselgreen and Moe (2006) investigated the use of conjunctions in the writing of Norwegian pupils aged 12/13 and 15/16, on levels A2 and B1, and concluded that regardless of level, the younger pupils used a distinctly narrower range of conjunctions than the older pupils. This is perhaps unsurprising, given that studies such as Nippold (2006) cited in Hasselgreen & Caudwell (2016), found that the development of conjunctions and adverbial conjuncts in English as a first language does not take off fully until adolescence. Table 2 contrasts a selection of conjunctions/adverbial conjuncts in coryl, for the different age groups.…”
Section: Interlanguage Analysismentioning
confidence: 69%
“…This may be the reason why an increasing body of research has been conducted into assessing young learners' proficiency in their new language, as documented in a special issue of Language Testing in 2000 and other publications (Hasselgreen 2005;McKay 2006). The most important question concerns what the construct to be measured is, as is discussed in detail by Inbar-Laurie and Shohamy in the present volume.…”
Section: Assessment In Ellmentioning
confidence: 97%
“…(eg. Hakuta et al, 2003;Hasselgreen, 2005;etc.) The CPH studies have brought much implication to the studies, especially empirical studies in Chinese EFL context.…”
Section: Discussionmentioning
confidence: 99%